2006
DOI: 10.1111/j.1540-8159.2006.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonfluoroscopic Catheter Navigation for Radiofrequency Catheter Ablation of Supraventricular Tachycardia in Children

Abstract: The use of a nonfluoroscopic system for catheter navigation significantly reduced fluoroscopy exposure and total procedure duration of RCA of common SVT substrates in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 17 publications
1
48
3
1
Order By: Relevance
“…An obvious aspect and indeed an advantage of the use of a mapping system are a significant reduction in fluoroscopy exposure for both patients and operators. In the field of electrophysiology, there are several papers based on randomized and non-randomized studies in adults [14,32] and paediatric populations [24,25], which demonstrate this advantage.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An obvious aspect and indeed an advantage of the use of a mapping system are a significant reduction in fluoroscopy exposure for both patients and operators. In the field of electrophysiology, there are several papers based on randomized and non-randomized studies in adults [14,32] and paediatric populations [24,25], which demonstrate this advantage.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, studies published in research literature have demonstrated that NMSs can confer the extra benefit of significantly reducing radiation exposure [10,14,32,33] during CA and also during paediatric electrophysiological procedures [9,13,24,25,26,30]. However, the use of NMSs during paediatric electrophysiological procedures is not a standard in many EP laboratories, and some colleagues are trying to reduce fluoroscopy exposure using low-dose fluoroscopy rather than utilizing NMSs [17,27,31].…”
Section: Introductionmentioning
confidence: 93%
“…Recently, it has been shown that non fluoroscopic electroanatomic (EA) mapping systems allows to reduce X-ray exposure for ablation procedures in children [10][11][12][13][14] . In addition, in few reports the feasibility of fluoroless procedures in children and adolescents has been demonstrated [14][15][16][17] , with a similar success and complication rate compared to conventional standard ablation procedures.…”
Section: Introductionmentioning
confidence: 99%
“…1 Other physicians reported successful ablation of right-sided supraventricular tachycardia using multiple catheters using virtual navigation with the EnSite NavX system (St. Jude Medical, St Paul, MN). [2][3][4][5] The subsequent addition of transesophaeal echo guidance facilitated nonfluoroscopic transseptal puncture for left-sided accessory pathway ablation, first reported in 2008. 6 These techniques were then adapted to catheter ablation of AF, and small series have demonstrated the feasibility of completely eliminating x-ray fluoroscopy for complex left atrial ablation using the combination of 3D mapping and intracardiac echocardiography.…”
Section: Evolving Nonfluoroscopic Techniquesmentioning
confidence: 99%